Absence of arbitrage valuation : a unified framework for pricing assets and securities - Glabadanidis, Paskalis; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Absence of Arbitrage Valuation presents a unified asset pricing strategy through absence of arbitrage and applies this framework to such disparate fields as fixed income security pricing, foreign exchange spots, and forward rates.
Keywords: Science